Intravascular Cooling Device Versus Esophageal Heat Exchanger for Mild Therapeutic Hypothermia in an Experimental Setting. (November 2019) - Schroeder, Daniel C.; Maul, Alexandra C.; Guschlbauer, Maria; Finke, Simon-Richard; de la Puente Bethencourt, David; Becker, Ingrid; Padosch, Stephan A.; Hohn, Andreas; Annecke, Thorsten; Böttiger, Bernd W.; Sterner-Kock, Anja; Herff, Holger
Abstract : BACKGROUND: Targeted temperature management is a standard therapy for unconscious survivors of cardiac arrest. To date, multiple cooling methods are available including invasive intravascular cooling devices (IVDs), which are widely used in the clinical setting. Recently, esophageal heat exchangers (EHEs) have been developed providing cooling via the esophagus that is located close to the aorta and inferior vena cava. The objective was to compare mean cooling rates, as well as differences, to target temperature during maintenance and the rewarming period of IVD and EHE. METHODS: The study was conducted in 16 female domestic pigs. After randomization to either IVD or EHE (n = 8/group), core body temperature was reduced to 33°C. After 24 hours of maintenance (33°C), animals were rewarmed using a target rate of 0.25°C/h for 10 hours. All cooling phases were steered by a closed-loop feedback system between the internal jugular vein and the chiller. After euthanasia, laryngeal and esophageal tissue was harvested for histopathological examination. RESULTS: Mean cooling rates (4.0°C/h ± 0.4°C/h for IVD and 2.4°C/h ± 0.3°C/h for EHE; P < .0008) and time to target temperature (85.1 ± 9.2 minutes for IVD and 142.0 ± 21.2 minutes for EHE; P = .0008) were different. Mean difference to target temperature during maintenance (0.07°C ± 0.05°C for IVD and 0.08°C ± 0.10°C for EHE; P = .496) and mean rewarming rates (0.2°C/h ± 0.1°C/h for IVD and 0.3°C/h ± 0.2°C/h for EHE; P = .226) were similar. Relevant laryngeal or esophageal tissue damage could not be detected. There were no significant differences in undesired side effects (eg, bradycardia or tachycardia, hypokalemia or hyperkalemia, hypoglycemia or hyperglycemia, hypotension, overcooling, or shivering). CONCLUSIONS: After insertion, target temperatures could be reached faster by IVD compared to EHE. Cooling performance of IVD and EHE did not significantly differ in maintaining target temperature during a targeted temperature management process and in active rewarming protocols according to intensive care unit guidelines in this experimental setting.